2017
DOI: 10.1016/j.bpsc.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 5 and Glutamate Involvement in Major Depressive Disorder: A Multimodal Imaging Study

Abstract: Background Preclinical and postmortem studies have implicated the metabotropic glutamate receptor 5 (mGluR5) in the pathophysiology of major depressive disorder (MDD). The goal of the present study was to determine the role of mGluR5 in a large group of individuals with MDD compared to healthy controls (HC) in vivo with [18F]FPEB and positron emission tomography (PET). Furthermore, we sought to determine the role glutamate plays on mGluR5 availability in MDD. Methods Sixty-five participants (30 MDD and 35 HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 52 publications
(67 reference statements)
3
60
2
2
Order By: Relevance
“…Previously, mGluR5 availability was reported to be lower in MDD (63,64). However, more recent studies have shown no differences between MDD and HC groups (65,66). Sample size limited examination of the additive effects of MDD in this study; however, future work should examine the potential effects.…”
Section: Discussionmentioning
confidence: 63%
“…Previously, mGluR5 availability was reported to be lower in MDD (63,64). However, more recent studies have shown no differences between MDD and HC groups (65,66). Sample size limited examination of the additive effects of MDD in this study; however, future work should examine the potential effects.…”
Section: Discussionmentioning
confidence: 63%
“…The metabotropic glutamate receptor type 5 (mGluR5) has emerged as a target of interest for PTSD and suicide research. mGluR5 is implicated in mood and anxiety symptoms in both human (3,4) and animal studies (5,6). We recently reported significantly higher mGluR5 availability in individuals with PTSD relative to matched controls across many brain regions (4).…”
mentioning
confidence: 98%
“…Differences between the effects of substances of abuse on mGlu5 might reflect their different pharmacodynamic profiles. Heterogeneous findings for the same substance of abuse may reflect differences in imaging methods, clinical heterogeneity of study samples 36 . Importantly, both human PET studies and animal models with different mGlu5 PET tracers and protocols showed normalization in mGlu5 after prolonged abstinence from alcohol abuse 18,22,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%